Analisis Komponen Penyusun Desain Kegiatan Laboratorium Enzim Katalase: (Analysis of the Components of the Catalyst Enzyme Laboratory Design Activity) - Eka Astika; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
The purpose of this study is to : (a) obtain an overview of the compatibility of the practical goals with the Basic Competencies developed in the design of laboratorium activities, (b) obtain an overview of the suitability of the practical goals and proceduaral steps with the concept to be achieved, (c) find out whether the design of laboratory activities used has supported knowledge construction based on an analysis of the componets in the design of laboratory activities. This research uses descriptive qualitative method through the ANCOR stages, namely Analysis, Trial, and Reconstruction of five catalase enzyme material laboratory design. The analysis carried out includes an analysis of the arious activities listed in the worksheet so that it can be seen how much these activities involve students in te science process, their relevance to the applicable curriculum, the relationship between the phenomena revealed and the concepts to be achieved and construct student knowledge. The instrument used is the modification of the instrument to analyze the suitability of pratikum activities with the curriculum and Diagram Vee to see whether the worksheet used constructs knowledge or not. The analysis included conceptual analysis, pratical analysis and knowledge construction analysis on various worksheet catalase enzyme tests. The catalase enzyme test practicum emphasizes students’ mastery of the catalase enzyme test material that is both principle and procedural, where students are required to be able to understand the properties of enzymes, factors that influence the work of enzymes, and the role of enzymes in metabolism. Thus it takes a series of competencies of students’ knowledge, skills and attitudes in mastering the catalase enzyme test material. For this reason, it requires a worksheet design that forms essential concepts so that they can achieve their goals and are in line with the demands of Basic Competence. Abstrak. Tujuan penelitian ini yaitu untuk: (a) memperoleh gambaran mengenai kesesuaian tujuan pratikum dengan Kompetensi Dasar yang dikembangkan dalam LKS, (b) memperoleh gambaran mengenai kesesuaian tujuan pratikum dengan langkah – langkah prosedural dengan konsep yang akan dicapai, (c) mengetahui apakah LKS yang digunakan sudah menunjang konstruksi pengetahuan berdasarkan analisis komponen-komponen dalam LKS. Penelitian ini merupakan penelitian Analisis Isi (Content Analysis). Analisis yang dilakukan meliputi analisis terhadap ragam kegiatan yang tertera dalam LKS sehingga dapat diketahui seberapa besar kegiatan tersebut melibatkan siswa dalam proses sains, relevansinya dengan kurikulum yang berlaku, hubungan antara fenomena yang diungkap dengan konsep yang akan dicapai dan mengkonstruksi pengetahuan siswa. Instrumen yang digunakan adalah modifikasi instrumen untuk menganalisis kesesuaian kegiatan pratikum dengan kurikulum dan Diagram Vee untuk melihat apakah LKS yang digunakan mengkonstruksi pengetahuan atau tidak. Analisis yang dilakukan meliputi analisis konseptual, analisis pratikal dan analisis konstruksi pengetahuan pada berbagai LKS uji enzim katalase. Pratikum uji enzim katalase menekankan pada penguasaan siswa terhadap materi uji enzim katalase yang bersifat prinsip serta prosedural, dimana siswa dituntut untuk mampu memahami sifat-sifat enzim, faktor-faktor yang mempengaruhi kerja enzim, serta peran enzim didalam metabolisme. Dengan demikian dibutuhkan serangkaian kompetensi pengetahuan, keterampilan, dan sikap siswa dalam menguasai materi uji enzim katalase. Untuk itu dibutuhkan desain LKS yang membentuk konsep – konsep esensial sehingga dapat mencapai tujuan dan sejalan dengan tuntutan Kompetensi Dasar.